Biological Fuel Cells and Membranes - Ghassemi, Zahra (Membranes (Basel), 2017)
Biofuel cells have been widely used to generate bioelectricity. Early biofuel cells employ a semi-permeable membrane to separate the anodic and cathodic compartments. The impact of different membrane materials and compositions has also been explored. Some membrane materials are employed strictly as membrane separators, while some have gained significant attention in the immobilization of enzymes or microorganisms within or behind the membrane at the electrode surface. The membrane material affects the transfer rate of the chemical species (e.g., fuel, oxygen molecules, and products) involved in the chemical reaction, which in turn has an impact on the performance of the biofuel cell. For enzymatic biofuel cells, Nafion, modified Nafion, and chitosan membranes have been used widely and continue to hold great promise in the long-term stability of enzymes and microorganisms encapsulated within them. This article provides a review of the most widely used membrane materials in the development of enzymatic and microbial biofuel cells.